Bonding performance of universal adhesive systems with dual-polymerising resin cements to various dental substrates: in vitro study - Shunsuke Takano; Rena Takahashi; Tomoko Tabata; Chen Zeng; Masaomi Ikeda; Yasushi Shimada (BMC Oral Health)
Abstract Background Resin cements often require substrate-specific pretreatment. Recently, universal adhesive systems have been introduced, simplifying procedures by eliminating the need for multiple adhesives and offering options that do not require light curing. This study investigated the bonding performance of universal adhesive systems combined with dual-polymerising resin cements on enamel, dentin, zirconia, lithium disilicate ceramics (LDS), and resin blocks. Methods Two universal adhesive and dual-polymerising resin cement combinations from the same manufacturer were tested: Bondmer Lightless II (BLII) with Estecem II (ECII), and Scotchbond Universal Plus adhesive (SBU) with RelyX Universal resin cement (RXU). Enamel, dentin, zirconia (Katana Zirconia UTML), LDS (IPS e.max CAD CEREC), and resin blocks (Katana Avencia P Block) were used as substrates. The universal adhesive was applied to all bonding surfaces, followed by resin cement application in micro-bore Tygon tubes and light curing for 40 s. Micro-shear bond strength (μSBS) was measured after 0 thermal cycles (0TC) or 10,000 thermal cycles (10kTC) (n = 20). Statistical analyses were conducted using t-tests and Welch's t-tests with Bonferroni correction (α = 0.05), and failure modes were examined. Results In the BLII/ECII group, the mean μSBS values exceeded 15 MPa for all substrates at 0TC. After thermocycling, μSBS increased significantly for the enamel (p < 0.05), remained unchanged for dentin and zirconia (p > 0.05) and decreased for LDS and resin blocks (p < 0.05). In the SBU/RXU group, 0TC μSBS values exceeded 15 MPa for enamel, zirconia, and resin blocks, but thermocycling significantly decreased μSBS for all substrates (p < 0.05). Comparison between BLII/ECII and SBU/RXU group showed no significant differences for enamel and resin blocks at 0TC (p > 0.05), but the BLII/ECII group exhibited higher SBS in the other groups (p < 0.05). Adhesive failure was the most frequently observed failure type across all groups. Conclusion The adhesive performance on diverse dental substrates including enamel, dentin, zirconia, LDS, and resin blocks was notably affected by the selection of universal adhesive systems in combination with dual-polymerising resin cements that were applied. The BLII/ECII combination demonstrated long-term stable bonding performance for enamel, dentin, and zirconia.